Effects of internal kinetics and muscle activity during the wide and narrow barbell back squat - Lahti, J. (2017)
Introduction. The barbell back squat (BBS) is a commonly utilized strength exercise to support general preparedness for the demands in multiple sports. Recently, studies have shown various strength training exercises have the potential to recruit the regions of the hamstrings differently. Specifically, it is unknown if changing stance width under conditions where forward knee movement is restricted engages the hamstring regions differently and how this corresponds with measured 3-D net joint moments (NJM) demands on the prime extensor joints. Therefore, the goal of this thesis is to investigate the acute effects of utilizing the wide barbell back squat (WBBS), and the narrow barbell back squat (NBBS) to femur parallel depth on the hip and knee musculature in a population of intermediate athletes. Methods.14 amateur rugby players (6 males, 8 females, age 27.36 ± 3.71 years; height: 174.1 ± 10.4 cm, body mass 81 ± 21.86 kg, squatting experience: 3.93 ±1.77 years) completed a 3-week familiarization period to learn controlled versions of femur parallel depth WBBS and NBBS. On the 4th week, all subjects completed a strict technical 1 RM test protocol for both widths on separate days. On the 5th week, all subjects performed WBBS and NBBS with 70% and 85% of 1-RM loads (shoeless, tempo 3-0-0), where biceps femoris long head (BFLH) and semitendinosus (ST) activity were recorded with 15-channel high-density electromyography (HD-EMG) with both overall and 5 channel regional divide (distal, medial proximal), 3-D net joint moments (NJM) of lower lumbar, hip and knee, and bipolar sEMG from gluteus maximus (GM) and vastus lateralis (VL). All sEMG was normalized and analyzed from the ascent phase. Results. The WBBS had higher hip flexion (85% load), hip abduction, and hip internal rotation (p<0.05). The NBBS had higher knee flexion and dorsiflexion (p<0.05). Ascent time changed with load but not descent time and no effects of width were noted (p>0.05). WBBS had higher activity in BLFH and ST overall, and in medial (85% load) and proximal (both loads) regions (p<0.05). Hamstring activity increased with load in the NBBS 85% BFLH proximal region, WBBS 85% BFLH overall, distal, ST overall, medial, and proximal regions (p<0.05). No hamstring regional interaction differences were found in all loads (p>0.05). At both loads, the WBBS had higher 3-D hip-to-knee NJM and hip-to-knee extensor NJM ratios (p<0.05). Hip-to-knee ratios did not increase with load (p>0.05). The WBBS had higher 3-D hip NJM, hip sagittal NJM, hip frontal NJM, hip transverse NJM, and knee frontal NJM (p<0.05). The NBBS had higher 3-D L5/SI NJM (85% load), 3-D knee NJM (85% load) and knee sagittal NJM (p<0.05). Both heavier loads of WBBS and NBBS had higher 3-D L5/SI NJM, 3-D hip NJM, hip sagittal NJM, and 3-D knee NJM (p>0.05). In the WBBS (70% load) GM activity was higher compared to the NBBS (p<0.05). Between the NBBS loads, GM activity increased with heavier load (p>0.05). VL activity did not change significantly between widths or load (p>0.05). Discussion and practical applications. Although reaching statistical significance, WBBS hamstrings activity was only at low levels, ranging with a mean of 26-38% of MVIC across loads. But considering the combined effect of the biomechanical differences, the WBBS around femur parallel depth might provide different long-term benefits compared to the NBBS. Specifically, sports that have high 3-D hip demands and knee stability demands, such as team or individual sports that involve multiple change of directions, should potentially vary stance width combined with control of forward knee movement in the barbell back squat to possibly gain more functionality in strengthening the lower limbs while not increasing the load on the lumbar. Long-term studies are needed to further confirm practical relevance.